Exploring adverse events associated with vosoritide monotherapy: Insights from the FDA Adverse Event Reporting System - Xiaomin Li; Xiangli Luo; Fei Liu; Chaolu Wang; Xiaoming Li; Huaixi Yu (PLoS ONE, 2026)
Background Dwarfism, a condition characterized by short stature, has been the focus of therapeutic advancements with the emergence of novel peptide drugs. Vosoritide, indicated for certain types of dwarfism, has shown therapeutic potential in clinical trials. However, a comprehensive safety profile is essential for its clinical application. The current literature lacks a detailed assessment of vosoritide’s safety, indicating a significant gap that this study aims to address. Methods We conducted a retrospective pharmacovigilance study by analyzing the FDA Adverse Event Reporting System (FAERS) database to evaluate adverse events (AEs) associated with vosoritide monotherapy. The study employed a case/non-case methodology and applied signal detection algorithms, including the Reporting Odds Ratio (ROR), Proportional Reporting Ratio (PRR), Bayesian Confidence Propagation Neural Network (BCPNN), and Multi-Item Gamma Poisson Shrinker (MGPS), to identify AE signals related to vosoritide use. Results The study included 9319269 reports from the FAERS database, covering the period from 2022 to 2023, with 274 reports specifically citing vosoritide. A significant number of AEs were identified, with a notable incidence in the pediatric population. The most frequently reported AEs were related to endocrine disorders, including altered growth hormone levels and glucose homeostasis issues. Other affected system organ classes (SOCs) were infections and infestations, as well as skin and subcutaneous tissue disorders. Specific preferred terms (PTs) associated with vosoritide included “growth deceleration,” “glycemic dysregulation,” and “local injection site reactions.” Conclusion The findings from this study underscore the importance of close monitoring of vosoritide treatment, particularly in pediatric patients. The identification of both expected and unexpected AEs highlights the necessity for ongoing pharmacovigilance and further research to fully understand the safety profile of vosoritide in clinical practice. This study contributes to the broader field by emphasizing the critical need for patient safety considerations in the development of new therapeutic agents.